IOT-Based Gemstone Detection and Analysis System - Irshad Hakeem; Ishika Manuel; Ravithamara Wijayabandu (International Journal of Engineering and Management Research, 2022)
“A gemstone is a mineral stone that be formed from the result of geological processes and has a hardness above 7 Mohs” [2]. [1] This current research is undertaken to create a system that can identify the gemstones of the Corundum Family. According to [2], there are four characteristics that can be used to identify the type of gemstone based on physical aspects. These four aspects are refraction of light, the color, density, and hardness of the mineral contained in the stone. One of the countries that produce the most gemstones and has the highest proportion of gemstones is Sri Lanka. There are 200 diverse types of gemstones around the globe, but only about 75 distinct kinds of coloured and colourless gemstones from 10 primary families could be discovered in Sri Lanka. Although Sri Lanka is naturally rich in the gemstone industry, the methods or techniques that are used to verify and validate gemstones are yet manual and traditional. The gemstone trade continues to thrive as miners and traders are far more knowledgeable about the different varieties of gemstone families. The method of verifying gemstones is fraught with challenges for both clients and traders. This research is conducted to invent an Internet of Things (IoT) based gemstone detector that can identify gemstones based on their refractive index, colour, and Cut-Shape, it is possible to effectively address the issues that customers and traders both confront. The refractive index, colour, and Cut-Shape of the gemstone will be determined via image processing, and the IoT device will be utilized to cluster the other elements.